Mystifications and misconceptions of lignin: revisiting understandings. Issue 21 (20th October 2022) - Souto, Felipe; Calado, Veronica
Abstract : Lignin is a tricky and complex structure. The growing interest in its use requires a unanimous approach to its nature; so, misconceptions that have already been overcome and those perpetuated by those who are not familiar with its complexity do not spread. Abstract : Science requires specialised terminologies to be precisely understood. Its specific vocabulary avoids one term having the same meaning for two different things. However, sometimes a misconception can occur and perpetuate by repetitive referencing citations without a sense of judgment. An apparent traditionalism seems to occlude updating. There are different terms to categorise and analyse lignin mistakenly. After more than 100 years, lignin reached a research and development peak. Many new concepts were obtained during this period, elucidating the potential of lignin. However, old decontextualised references insist on using approaches distant from scientific progress. Furthermore, the redundancy of misunderstandings prevents the continuity and development of research on lignin because of the information heterogeneity. This review does not claim to exhaust all the lignin mishaps; there are many! Nevertheless, it revisits the main misconceptions that are notoriously evidenced as an incentive to take a closer look at future appreciations. Is lignin a macromolecule or a polymer? Does it have a melting temperature? How does its structure look? These are some questions that this review seeks to revisit and answer.